Cover Picture: Diazirines as Potential Molecular Imaging Tags: Probing the Requirements for Efficient and Long‐Lived SABRE‐Induced Hyperpolarization (Angew. Chem. Int. Ed. 40/2017). Issue 40 (1st August 2017) - Shen, Kun; Logan, Angus W. J.; Colell, Johannes F. P.; Bae, Junu; Ortiz, Gerardo X.; Theis, Thomas; Warren, Warren S.; Malcolmson, Steven J.; Wang, Qiu
Abstract : Diazirines are an attractive class of potential molecular tags for magnetic resonance imaging owing to their biocompatibility and ease of incorporation into a large variety of molecules. In their Communication onpage 12112 ff., W. S. Warren, S. J. Malcolmson, Q. Wang, and co‐workers show with a 15 N2 ‐diazirine‐containing choline derivative that 15 N2 ‐diazirine motifs are capable of supporting long‐lasting polarization by the simple SABRE‐SHEATH hyperpolarization method, making then promising as tags for NMR/MRI imaging.